Zinc and other micronutrients supplementation through the use of sprinkles: impact on the occurrence of diarrhea and respiratory infections in institutionalized children - Danile L.B. Sampaio; Ângela P. de Mattos; Tereza Cristina M. Ribeiro; Maria Efigênia de Q. Leite; Conrad R. Cole; Hugo Costa-Ribeiro, Jr (Elsevier, 2013)
Objective: To evaluate the incidence of diarrheal disease (DD) and acute respiratory infection (ARI) in children undergoing supplementation of zinc and other micronutrients through the use of sprinkles, as well as their acceptance by these patients. Method: This was a randomized double-blinded clinical trial of 143 healthy institutionalized children, aged 6 to 48 months. They were randomized into two groups and received daily zinc and micronutrients - test group (sprinkles), or micronutrients without zinc - control group. Children were supplemented for 90 days and followed regarding the outcomes of DD and ARI. Results: Of the randomized children, 52.45% belonged to the test and 47.55% to the control group. The incidence of DD in the test group was 14.7% and was 19.1% in the control group. The test group showed a lower risk of developing DD when compared to controls, but this finding was not statistically significant (RR = 0.77 [0.37 to 1.6], p = 0.5088). ARI had high incidence in both groups, 60% in the test group and 48.5% in the control group, with an increased risk of developing the disease in the test group, but with no statistical significance (RR = 1.24 [0.91 to 1.68], p = 0.1825). Regarding acceptance, the mean percentage of consumption, in days, of the entire content of the sachets containing sprinkles was 95.72% (SD = 4.9) and 96.4% (SD = 6.2) for the test and control groups, respectively. Conclusions: Zinc supplementation through the use of sprinkles did not reduce the incidence of DD or ARI among the evaluated children. The sprinkles were well accepted by all study participants. Resumo: Objetivo: Avaliar a incidência de doenças diarreicas (DA) e infecção respiratória aguda (IRA) em crianças submetidas à suplementação de zinco e outros micronutrientes através dos sprinkles, bem como a aceitação destes pelos pacientes. Método: Ensaio clínico, duplo cego, randomizado, realizado com 143 crianças institucionalizadas, saudáveis, de seis a 48 meses. As mesmas foram randomizadas em dois grupos e receberam diariamente zinco + micronutrientes - grupo teste (sprinkles), ou apenas micronutrientes sem zinco - grupo controle. As crianças foram suplementadas por 90 dias e acompanhadas quanto aos desfechos de DA e IRA. Resultados: Das crianças randomizadas, 52,45% pertenciam ao grupo teste e 47,55% ao controle. A incidência de DA no teste foi de 14,7%, e no controle, 19,1%. O grupo teste apresentou menor risco de desenvolver DA em relação ao controle, porém esse achado não foi estatisticamente significante (RR = 0,77 [0,37-1,6]; p = 0,5088). A IRA apresentou incidência elevada em ambos os grupos, sendo 60% no teste e 48,5% no controle, com risco maior de apresentar a doença no grupo teste, porém sem significância estatística (RR = 1,24 [0,91-1,68]; p = 0,1825). Quanto à aceitação, o percentual médio de consumo, em dias, de todo conteúdo dos sachês contendo sprinkles foi 95,72% (DP = 4,9) e 96,4% (DP = 6,2), para o teste e controle, respectivamente. Conclusões: A suplementação de zinco através dos sprinkles não reduziu a incidência de DA ou IRA entre as crianças avaliadas. Os sprinkles foram bem aceitos por todos os participantes do estudo. Keywords: Zinc supplementation, Diarrhea, Respiratory infection, Zinc deficiency, Palavras-chave: Suplementação de zinco, Diarreia, Infecção respiratória, Deficiência de zinco